2002
DOI: 10.3354/ame028249
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of attachment of potentially toxic bacteria to Alexandrium tamarense

Abstract: Interactions between bacteria and harmful algae are potentially important regulating factors for population dynamics of both organisms and for toxin production. These interactions are still poorly understood. To monitor the physical associations between potentially toxic bacteria and dinoflagellates in controlled conditions, we inoculated an axenic non-toxic strain of Alexandrium tamarense (Dinophyceae) together with reputed paralytic shellfish toxin (PST)-producing bacteria belonging to the genus Alteromonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…M. aeruginosa influence on heterotrophic bacterial growth was very limited during the exponential phase of the experiment but strongly increased heterotrophic bacterial growth during the stationary phase. A similar bacterial growth characteristic was found in coculture of a dinoflagellate and bacteria (Simon et al, 2002), which suggested that heterotrophic bacterial growth was supported by organic matter derived from algal or cyanobacterial cells (Cole, 1982). The stimulation of M. aeruginosa growth by heterotrophic bacteria took place at the initiation of the exponential phase when heterotrophic bacteria grew slowly and bacterial diversity was high.…”
Section: Interactions Between Microcystis and Heterotrophic Bacterialmentioning
confidence: 50%
“…M. aeruginosa influence on heterotrophic bacterial growth was very limited during the exponential phase of the experiment but strongly increased heterotrophic bacterial growth during the stationary phase. A similar bacterial growth characteristic was found in coculture of a dinoflagellate and bacteria (Simon et al, 2002), which suggested that heterotrophic bacterial growth was supported by organic matter derived from algal or cyanobacterial cells (Cole, 1982). The stimulation of M. aeruginosa growth by heterotrophic bacteria took place at the initiation of the exponential phase when heterotrophic bacteria grew slowly and bacterial diversity was high.…”
Section: Interactions Between Microcystis and Heterotrophic Bacterialmentioning
confidence: 50%
“…and Thalassobius aestuarii were key factors that caused the lysis (Wang et al, 2010c). Many bacterial isolates have been proved to have the capability to kill microalgae (algicidal activity) by different ways (Amaro et al, 2005;Lovejoy et al, 1998;Simon et al, 2002;Skerratt et al, 2002). Certain algicidal bacterial strains (e.g.…”
Section: Lysis/killing Of Microalgae By Algicidal Bacteriamentioning
confidence: 99%
“…Algicidal bacteria are regarded as one of the key biological agents in the dramatic termination of microalgal blooms (1). Algicidal bacteria either directly attack and kill microalgae or produce special compounds to lyse microalgae (2,34,36). Some other nonalgicidal bacteria can inhibit microalgal growth by changing the microenvironment of microalgae (11) or by competing with microalgae for nutrients (9,18).…”
mentioning
confidence: 99%